Characterization of saliva in immunocompromised patients and tobacco users: A case-control study - Abha Rani; Mamatha Gowda Panchaksharappa; Neetha Mellekatte Chandrashekarappa; Rajeshwari G Annigeri; Varsha Kanjani (Wolters Kluwer Medknow Publications, 2019)
Objective: The aim of the study was to assess salivary flow rate, salivary pH, and salivary albumin concentration in systemically compromised subjects and tobacco users and its comparison to healthy controls. Materials and Methods: Sixty patients were selected and then were equally divided into systemically compromised group, tobacco users, and control group with 20 in each group. Saliva flow rate was assessed using modified Schirmer test (MST), salivary pH was estimated by pH meter, and salivary albumin concentration was determined using bromocresol green method. Results: The salivary flow rate readings measured by MST were 22.65 ± 2.79, 22.6 ± 3.57, and 33.22 ± 2.30 mm/3min in systemically compromised individuals, tobacco users, and control group, respectively (P < 0.001). The salivary pH was 6.80 ± 0.24, 6.81 ± 0.25, and 7.18 ± 0.17 in systemically compromised subjects, tobacco users, and control group, respectively (P < 0.001). The salivary albumin concentration was 2.49 ± 0.61, 0.73 ± 0.13, and 1.14 ± 0.12 g/dl in systemically compromised subjects, tobacco users, and control group, respectively (P < 0.001). Conclusion: MST can be routinely used as chair-side investigation to evaluate salivary flow which is objective, inexpensive, easy-to-perform, and patient-friendly. The salivary flow rate, salivary pH, and salivary albumin level in systemically compromised subjects, tobacco users, and normal individuals showed significant differences.